Medroxyprogesterone acetate alone or synergistic with chemotherapy suppresses colony formation and DNA synthesis in C6 glioma in vitro - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
We have studied the effects of medroxyprogesterone acetate (MPA) on C6 glioma growth in vitro in order to prove the hypothesis that it could arrest growth and induce drug sensitisation in a glial tumour as it does in breast cancer cells. Plating, thymidine-labelling index, ultra-structure, and soft agar colony growth were determined after incubation with MPA, and/or cisplatin, procarbazine and methotrexate (MTX). MPA (1 mug/ml) reduced the thymidine-labelling index by 41 and 73% at 48 and 96 h, respectively, and decreased colon growth by 61%. Soft agar colony inhibition by NIPA was almost as potent as MTX (0.3 mug/ml), but the latter drug showed very high cytotoxicity. Electron ri-i-icroscopy revealed that in medroxyprogesterone treated cells myeloid bodies developed, but MTX treatment caused mainly necrosis. Medroxyprogesterone increased procarbazine and cisplatin-induced colony growth and S-phase inhibition, but reduced MTX-induced thymidine-labelling inhibition. In conclusion, progesterone may inhibit growth and sensitize to drugs. (C) 2001 ISDN. Elsevier Science Ltd. All rights reserved.
Keywords: medroxyprogesterone; chemotherapy; procarbazine; BREAST-CANCER; PARTIAL RESISTANCE; ASTROCYTIC TUMORS; GLIAL-CELLS; DEXAMETHASONE; PROGESTERONE; EXPRESSION; RECEPTOR; DIFFERENTIATION; APOPTOSIS